Model Simulasi Pengembangan Sistem Irigasi untuk Tanaman Jagung di Lahan Sawah dan Lahan Kering (Studi Kasus Pada Usahatani Jagung di Kabupaten Kediri) - Agung Prabowo; Sigit Supadmo Arif; Lilik Sutiarso; Bambang Purwantana (agriTECH, 2014)
Corn crop irrigation system in Kediri has not been able to support its productivity to meet the needs of the animal feed industry raw materials in East Java. To achieve the sustainability of corn crop irrigation system development is required planning through appropriate systems approach. The purpose of this research is to build a simulation model of corn crop irrigation system development in paddy field and dry land to increase production and incomes of farmers. The method used in this study is the method of system approach. System approach was used to formulate the simulation model of an irrigation system for corn crops. The time limit of simulation model was started in 2012 until 2035. The structure of the model was grouped into four sub models, namely: environment, technology, farming and management. In this simulation model was conducted in 4 scenarios: 1) control, 2) increasing the Cropping Intensity (CI) of corn 20% and the development of pump irrigation in dry land, 3) increasing CI of corn 20% and the development of pump irrigation in dry land and the paddy field, and 4) increasing CI of corn 20% and the development of pump irrigation in dry land and utilizing an existing irrigation network in the paddy field. Measuring tools for success in development of the irrigation system are the highest increase for maize production and farmer’s income. From this result it was concluded that scenario 4 was the best scenario to be implemented because it can increase the production was 114.33% and farmer income was 130.93% with an investment cost of Rp. 1141.27, -/kg of corn.ABSTRAKSistem irigasi tanaman jagung yang ada di Kabupaten Kediri belum mampu mendukung peningkatan produksi untuk memenuhi kebutuhan bahan baku industri pakan ternak di Jawa Timur. Untuk mencapai keberhasilan program pengembangan sistem irigasi tanaman jagung tersebut diperlukan perencanaan melalui metode pendekatan sistem yang tepat. Tujuan penelitian ini adalah membangun model simulasi pengembangan sistem irigasi tanaman jagung di lahan sawah dan lahan kering untuk meningkatkan produksi dan pendapatan petani jagung. Metode yang digunakan dalam penelitian ini adalah metode pendekatan sistem. Pendekatan sistem digunakan untuk merumuskan model simulasi pengembangan sistem irigasi untuk tanaman jagung. Batasan waktu model simulasi ini dimulai pada tahun 2012 sampai dengan 2035. Struktur model dikelompokkan menjadi empat submodel, yaitu: lingkungan, teknologi, usahatani dan pengelolaan. Pada model simulasi ini dilakukan 4 skenario, yaitu : 1) kontrol, 2) meningkatkan intensitas penanaman (IP) jagung 20% dan pengembangan irigasi pompa di lahan kering, 3) meningkatkan IP jagung 20% dan pengembangan irigasi pompa di lahan kering serta di lahan sawah, dan 4) meningkatkan IP jagung 20% dan pengembangan irigasi pompa di lahan kering dan memanfaatkan jaringan irigasi yang ada di lahan sawah. Sebagai tolok ukur keberhasilan pengembangan sistem irigasi tersebut adalah terjadi peningkatan yang tertinggi untuk produksi dan pendapatan petani jagung. Dari hasil penelitian ini diperoleh kesimpulan bahwa skenario 4 merupakan yang terbaik untuk dilaksanakan karena mampu meningkatkan produksi 114,33% dan pendapatan petani 130,93% dengan biaya investasi Rp. 1.141,27,-/kg jagung.